2011
DOI: 10.1007/s11121-011-0239-0
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment and Retention of Latino Immigrant Families in Prevention Research

Abstract: The development and testing of culturally competent interventions relies on the recruitment and retention of ethnic minority populations. Minority immigrants are a population of keen interest given their widespread growth, needs, and contributions to communities in which they settle, and particularly recent immigrants from Mexico and Central and South American countries. However, recruitment and retention strategies for entirely immigrant samples are rarely discussed in the literature. The current article desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
88
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(91 citation statements)
references
References 18 publications
2
88
1
Order By: Relevance
“…Identifying where immigrants are, so as to target them specifically, was a primary challenge for many studies we reviewed. Several studies have turned to non-probability convenience sampling and self-selection partly guided by personal contacts with immigrants (e.g., snowball sampling), immigrant community liaisons (e.g., community centers or churches with large populations of immigrants), and other Bgatekeepers^ [34][35][36]. In seeking to make contact with possible participants, some studies found recruitment through advertising to be unsuccessful and transitioned to snowball sampling to identify study participants [37].…”
Section: Pre-recruitment Activitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Identifying where immigrants are, so as to target them specifically, was a primary challenge for many studies we reviewed. Several studies have turned to non-probability convenience sampling and self-selection partly guided by personal contacts with immigrants (e.g., snowball sampling), immigrant community liaisons (e.g., community centers or churches with large populations of immigrants), and other Bgatekeepers^ [34][35][36]. In seeking to make contact with possible participants, some studies found recruitment through advertising to be unsuccessful and transitioned to snowball sampling to identify study participants [37].…”
Section: Pre-recruitment Activitiesmentioning
confidence: 99%
“…Finally, many studies on immigrants find recruiting their target sample size often leads to extending their project timeline. Both the experts we interviewed (e.g., NLAAS) and one of the studies reviewed [35] recommended that other researchers should include a large budget for the cost of recruiters and data collectors in order for them to have the time to establish a good rapport with participants.…”
Section: Reducing Barriers To Participationmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Research engagement with immigrants is quite challenging owing to mistrust of medical professionals, power differentials between researchers and participants, difficulty penetrating isolated communities, language barriers, and small available sample sizes. 15,20,21 Research recruitment of undocumented populations is even more challenging given fears related to engagement with government and health care organizations, concerns about disclosing documentation status, discrimination, and competing economic and social demands for their time. 15,16,[22][23][24] Community-based recruitment has been successful in some studies with broader Latino samples and is likely to be critical to research with subsets of immigrant populations such as those without documentation.…”
mentioning
confidence: 99%
“…15,16,[22][23][24] Community-based recruitment has been successful in some studies with broader Latino samples and is likely to be critical to research with subsets of immigrant populations such as those without documentation. 9,20,21,25,26 As a difficult-to-reach and understudied population, it is also important to elucidate how to engage them, not only in available health care programming, but also in research that contributes to the development of policies that improve their health care access. This paper details the participant engagement strategies and research challenges of a research team studying DACA-eligible Latinos.…”
mentioning
confidence: 99%